Analisis dan Perancangan Sistem Informasi Akuntansi Pengelolaan Keuangan Pada BUMDes Sari Merta Dana Utama Desa Sumerta Kauh - Budiartini, Ni Kadek Ayu; Krisna Juliharta, I Gede Putu; Kusuma, Ni Putu Noviyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
An accounting information system is a system that processes data and transactions to produce information that is useful for planning, controlling and operating a business. Currently there are still village governments that have not implemented an accounting information system properly, one of which is Bumdes Sari Merta Dana Utama Sumerta Kauh Village. Sari Merta Dana Utama is a village business institution managed by the community and village government and formed based on the needs and potential of the village. Currently Sari Merta Dana Utama is experiencing several obstacles in their financial management system. The aim of this research is to design a financial management accounting information system, so that it can make it easier for Bumdes Sari Merta Dana Utama to record and facilitate monitoring of financial income and expenditure at Bumdes.